Penyelamatan Kredit Bermasalah Pada Lembaga Perkreditan Desa (LPD) Pasca Pandemi Covid-19 di Desa Adat Ped Kecamatan Nusa Penida Kabupaten Klungkung - I Nyoman Sujana; I Wayan Kartika Jaya Utama (Postgraduated Community Service Journal, 2022)
The tourism business is the mainstay of the Small Island of Nusa Penida as an inseparable part of the Island of the Gods, Bali. The existence of the COVID-19 Pandemic has made Bali tourism and is no exception also an impact on the tourism business in Nusa Penida. The people's economy in Nusa Penida experienced very severe shocks and even eroded almost all economic sectors; including the impact on the financial services sector owned by a traditional village called the Village Credit Institution (LPD). Bali tourism, especially Nusa Penida as one of the world's tourist destinations during the COVID-19 Pandemic, has drained the energy of the management of Traditional Village LPDs throughout Bali, because many people from Traditional Villages have lost their purchasing power as a result of COVID-19, so that the principle of good faith in the world business is often neglected and even overtaken by the demands of the bowels. After the COVID-19 pandemic era, many LPD administrators were faced with a dilemma between saving LPD operations due to the large number of problem loans with a sense of empathy for indigenous village residents who were unable to pay credit installments as a result of loss of income as a result of COVID-19. Even though the COVID-19 pandemic has passed on the surface, the feeling of anxiety about the emergence of a new variant continues to create anxiety among LPD administrators. Related to this dilemma, this paper examines legal issues related to "rescuing problem loans" faced by LPDs after the COD-19 pandemic occurred in the tourist area of Nusa Penida Island. This legal issue will be studied using a normative legal approach supplemented by a sociological approach carried out by LPD administrators throughout the Nusa Penida District, Klungkung Regency -Bali.